THE ROLE OF ANXIETY IN ENGLISH LANGUAGE WRITING SKILL AT SECONDARY LEVEL STUDENTS - Syed Shahid Nawaz (UC Journal: ELT, Linguistics and Literature Journal, 2021)
This study has investigated the role of English language anxiety, its types and impacts on writing skill at secondary school level. Quantitative approach was used in this study. One hundred seventeen students and twenty teachers of English Language were selected randomly in this study. Questionnaire was used as data collection tool. It was adapted from Cheng (2004) in a modified form of English language writing anxiety (i.e. second language writing anxiety inventory) to analyze the causes and effects of English language writing anxiety. Another questionnaire was used to collect data from teachers, which were related with English language writing anxiety in their students. Consequently, the findings confirmed that most of the students feel anxiety, which had a debilitating impact on English language writing. Similarly, evaluation of data discovered that somatic anxiety, cognitive anxiety, insufficient writing practice, avoidance behavior, loss of vocabulary expertise in the performance of writing represent the primary sources of anxiety in English language writing by students. Moreover, this research showed that very few teachers seem to assist their students’ triumph over writing anxiety because of massive elegance and the limited time allocated for English classrooms. On the basis of the findings, a few suggestions made so as to help to lessen anxiety in English language writing classrooms. The suggestions for classrooms exercise centered on ways of handling English language writing anxiety and guidelines to make the writing magnificence and to create a good environment for stressful students.